Acquisitionism vs anti-acquisitionism: Where does phonological change occur? - 최재혁 (Studies in Phonetics, Phonology, and Morphology, 2018)
In this study, I investigate the debate of the locus of linguistic change. For example, Hale (2003) and Reiss (2003) insist that linguistic change only happens during first language acquisition. On the contrary, Sankoff (2005) and Bybee (2007) argue that linguistic change occurs over the lifespans of individuals. Despite the fact that many who have written on the issues discussed in this study have argued that all endogenous linguistic change occurs in the first language acquirer, I have tried to present evidence that this is mistaken, and that change can (but need not necessarily always) occur in an adult grammar, specifically the internal grammar of speakers. KCI Citation Count: 0